Understanding the colonial debate in postcolonial France (2016)
Recent debates on colonialism and its repercussions in contemporary French societies have indicated a high level of postcolonial activities in France. However, the adoption and use of postcolonial theory by French critics is insignificant compared to its strides in the English-speaking world. This study examines recent opinions of French intellectuals on their colonial history with a view to establishing the trends in postcolonial criticism in the French literary world. The study adopted postcolonial criticism in as much as the issues discussed revolve round the aftermath of colonialism on the French societies. The low patronage of postcolonial theory in France was premised on the apathy of the French academics against a perceived Anglo-saxon invention, and the official posture of the French government to praise colonial adventure. The analysis also covered the anti-colonial intellectuals’ opinions about the French postcolonial identity, the re-appraisal of colonial history and efforts at decolonising the minds of the French society, including its government. The reflection of postcolonial issues in contemporary French societies provides a background to further the appreciation of literary works by postcolonial French writers such as Le Clézio and Michel Tournier.